Marine sanctuaries boon or bane? : an evaluation of the effects of the marine sanctuary on the socio-economic conditions of the fisherfolks in Naba, Culasi, Antique - Tordesillas, Janet S. (University of the Philippines in the Visayas, 2002)
The study was conducted to determine the effects of the marine sanctuary establishment on the certain indicators of socio-economic conditions of the fisherfolks of Naba,Culasi, Antique and their attitude towards marine sanctuary establishment.. The descriptive research design and survey technique for data gathering were utilized in this study. A structured interview schedule was used as the instrument for collecting data. Forty-three out of 79 registered fisherfolks served as respondents. The Naba marine sanctuary which was established two yers go was chosen as the study site in order to determine midstream effects of the project. The results showed that there was a high acceptance of the marine sanctuary establishment in the area. As a result of the marine sanctuary establishment, an increase of as much as 20% in income was reported by some of the respondents. However, alternative livelihood activities did not succeed in the area; rather, the respondents resorted to supplemental livelihood schemes to augment their income when restriction on fishing was imposed. The perceived changes in socilal conditions were the improvement in the means of providing sustenance, increased financial capability to send children to school, improved shelter, increased recreation opportunities and increased means in providing daily necessities. Institutional participation of the respondents improved from 65% in marine sanctuary establishment to 81% iin marine sanctuary management. The marine sanctuary has lso contributed to community empowerment as manifested by the increased environmental awareness and knowledge of relevant fishery laws, positive changes in perception and behavior towards environmental conservation activities and CRM project imoplementation, and, improved interpersonal relationship with fellow residents. The establishment and management of the marine sanctuary have also brought about increased capability for collective action on common issues that affect their lives as a community. The enhancement of supplemental livelihood options raher than the provision of alternative livelihood schemess should be seriously considered in similar programs given the limited skills of the fisherfolks. Continued environmental education, implementation of zoning to pronote equal distribution of benefits from the marine sanctuary, and capability building for fisherfolks are likewise recommended to ensure sustainability of the project. Also, a similar study to be done after three years will determine more tangible benefits, with the results of this study to serve s baseline for analysis.